Prophecy, alchemy, and the end of time : John of Rupescissa in the late Middle Ages - DeVun, Leah (Columbia University Press, 2009)
In the middle of the fourteenth century, the Franciscan friar John of Rupescissa sent a dramatic warning to his followers: the last days were coming; the apocalypse was near. Deemed insane by the Christian church, Rupescissa had spent more than a decade confined to prisons & mdash;in one case wrapped in chains and locked under a staircase & mdash;yet ill treatment could not silence the friar's apocalyptic message. Religious figures who preached the end times were hardly rare in the late Middle Ages, but Rupescissa's teachings were unique. He claimed that knowledge of the natural wo.